Modern Breast Cancer Surgery 1st Central-Eastern European Professional Consensus Statement on Breast Cancer - Zoltán Mátrai; Péter Kelemen; Csaba Kósa; Róbert Maráz; Attila Paszt; Gábor Pavlovics; Ákos Sávolt; Zsolt Simonka; Dezső Tóth; Miklós Kásler; Andrey Kaprin; Petr Krivorotko; et al. (Frontiers Media S.A., 2022)
This text is based on the recommendations accepted by the 4th Hungarian Consensus Conference on Breast Cancer, modified on the basis of the international consultation and conference within the frames of the Central-Eastern European Academy of Oncology. The recommendations cover non-operative, intraoperative and postoperative diagnostics, determination of prognostic and predictive markers and the content of cytology and histology reports. Furthermore, they address some specific issues such as the current status of multigene molecular markers, the role of pathologists in clinical trials and prerequisites for their involvement, and some remarks about the future.